2021
DOI: 10.3389/fendo.2021.739629
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Hypothyroidism With Cardiovascular Diseases in the Offspring

Abstract: BackgroundNo previous study has examined the effect of maternal hypothyroidism on a broad spectrum of cardiovascular disease (CVD) endpoints in the offspring.MethodsA nationwide population-based cohort study based on the linkage of several Danish nationwide registries was conducted to explore whether maternal hypothyroidism is associated with offspring’s CVD. Altogether 1,041,448 singletons born between the 1st of January 1978 and the 31st of December 1998 were investigated from the age of 8 years to the 31st … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…[9][10][11][12][13][14] Maternal thyroid hormones are crucial for the process of brain development, metabolic regulation, cardiovascular function, as well as normal growth and maturation of bones. [14][15][16][17][18] Profound consequences on the health of the offspring arise from a complete dependence of the fetus on maternal thyroid hormones until the second trimester of pregnancy in humans and mid-gestation in mice, and sustained influence of maternal thyroid hormones at later stages. 19,20 Accumulating evidence from humans and other mammals indicates that maternal serious thyroid hormone deficiencies (e.g., maternal hypothyroidism) can be hazardous for the future cognitive performance of the offspring, such as cretinism and mental retardation.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Maternal thyroid hormones are crucial for the process of brain development, metabolic regulation, cardiovascular function, as well as normal growth and maturation of bones. [14][15][16][17][18] Profound consequences on the health of the offspring arise from a complete dependence of the fetus on maternal thyroid hormones until the second trimester of pregnancy in humans and mid-gestation in mice, and sustained influence of maternal thyroid hormones at later stages. 19,20 Accumulating evidence from humans and other mammals indicates that maternal serious thyroid hormone deficiencies (e.g., maternal hypothyroidism) can be hazardous for the future cognitive performance of the offspring, such as cretinism and mental retardation.…”
Section: Introductionmentioning
confidence: 99%
“…The values of TSH and FT4 in newborns of the treated mothers have been observed signi cantly different from the controls despite adequate supplementation 10 . Further, an increased risk of cardiovascular diseases like hypertension, arrhythmia, and myocardial infarction has been identi ed in infants due to maternal hypothyroidism 11 . Khatiwada et al 12 conducted a study to examine the thyroid function and breast milk composition of mothers with hypothyroidism and found lower levels of T4 in their breast milk compared to euthyroid mothers 12 .…”
Section: Introductionmentioning
confidence: 99%
“…3 A population-based cohort study conducted by Miao et al showed that the risk of cardiovascular disease and hypertension risk was 1.71 times higher in newborns from mothers with maternal hypothyroidism. 4 Another recent study reported that the risk of congenital anomalies in fetuses of mothers with maternal hypothyroidism was 22%, and cardiac anomalies constituted a significant portion of these congenital anomalies. 5 Ersak et al evaluated the right and left cardiac outputs of the fetuses of pregnant women with maternal hypothyroidism in their study and determined both right and left cardiac outputs to be significantly lower than the control group fetuses and stated that the cardiac output of the fetus could be affected by maternal hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…A population‐based cohort study conducted by Miao et al. showed that the risk of cardiovascular disease and hypertension risk was 1.71 times higher in newborns from mothers with maternal hypothyroidism 4 . Another recent study reported that the risk of congenital anomalies in fetuses of mothers with maternal hypothyroidism was 22%, and cardiac anomalies constituted a significant portion of these congenital anomalies 5 .…”
Section: Introductionmentioning
confidence: 99%